Comparison of mechanistic pathways of metabolic bariatric surgery in diabetic patients. (3rd October 2022) - Chew, N W S; Lin, C X; Yeong, T; Lim, W H; Ng, C H; Chin, Y H; Muthiah, M; Loh, P H; Mok, S F; Shabbir, A; Khoo, C M; Foo, R
Abstract: Background and aims: Metabolic bariatric surgeries are potentially efficacious treatment options in patients with type 2 diabetes mellitus (T2DM). However, previous meta-analyses focused on individual operative approaches rather than the mechanistic pathways behind different bariatric procedures. Thus, this updated network meta-analysis aimed to synthesize new evidence and comparatively evaluate the efficacy of bypass against restrictive procedures and standard first-line treatment for patients with T2DM. Methods: Embase, Medline and trial registries were searched for randomized controlled trials on bariatric surgeries in patients with T2DM. A Bayesian network meta-analysis was conducted to compare between bypass, restrictive bariatric procedures, medical therapy and lifestyle intervention. Primary outcomes were T2DM remission and improvements in glycated haemoglobin (HbA1c). Secondary outcomes included changes in body mass index (BMI), lipoprotein levels and blood pressure. Results: Thirty-two articles comprising 2, 071 patients were included. Bypass surgery was statistically superior to restrictive procedures (RR: 2.57, 95% CrI: 1.36 to 5.43), medical therapy (RR: 35.29, 95% Crl: 10.56 to 183.23), and lifestyle intervention (RR: 40.51, 95% Crl: 5.32 to 402.59) in T2DM remission. Both bypass surgery and restrictive procedures were largely comparable in lowering HbA1c (MD: 0.02, 95% Crl: −0.03 to 0.08). In addition, bypass surgery significantly lowered BMI and blood pressure compared to other interventions. While restrictive procedures significantly increased high-density lipoproteins compared to bypass surgery, lifestyle intervention and bypass surgery were statistically superior to restrictive procedures in reducing low-density lipoproteins. Conclusion: This study demonstrates that bypass surgery is superior to restrictive bariatric procedures in diabetes remission and glycaemic control. Additionally, significant metabolic advantages support the choice of bypass surgery over restrictive bariatric procedures in T2DM management. Funding Acknowledgement: Type of funding sources: None.